Surgical Management Of Obesity Comparative Outcomes Of Bariatric Procedueres (Journal of Pharmaceutical Negative Results, 2022)
Background: That is why obesity as a condition has become one of the major threats to human health for people living in different countries. Bariatric surgery can be ultimately recommended for weight loss as well as for the improvement of obesity associated limited morbidity in case the conservative therapies are ineffective.Objectives: The various bariatric surgeries performed include the Laparoscopic adjustable gastric band, Laparoscopic sleeve gastrectomy, Laparoscopic roux-en-Y gastric bypass, Open roux-en-Y gastric bypass and Biliopancreatic diversion with duodenal switch, in order to assess the efficacy, the complications involved and the weight loss and obesity comorbidities’ alteration from one procedure to another.Study design: This was a observational study.Place and duration of study. Department of Surgery QHAMC, Nowshera Medical college ,Nowshera from jan 2020 to jan 2021Methods: : The various bariatric surgeries performed include the Laparoscopic adjustable gastric band, Laparoscopic sleeve gastrectomy, Laparoscopic roux-en-Y gastric bypass, Open roux-en-Y gastric bypass and Biliopancreatic diversion with duodenal switch, in order to assess the efficacy, the complications involved and the weight loss and obesity comorbidities’ alteration from one procedure to another.Results: Mean patient age was 42.3 years old (SD=8.5). RYGB experienced the highest weight loss, but when comparing the weight loss to SG and AGB, there was a statistically significant difference (p < 0.01). Among all the variables, SG demonstrated moderate utility within the organization and AGB had the least impression. RYGB also had better comorbidity management (for example diabetes, hypertension).Conclusion: In the management of obesity, bariatric surgery proven as beneficial, and RYGB yields the maximum benefits concerning weight loss and comorbidity treatment. Carrying through individualized approach to the choice of the procedure and subsequent Superovulation monitoring is critical.